Rurality, Ethnicity, and Gender Patterns of Cultural Continuity during the “Great Disjuncture” in the R.M. of Hanover, 1945-1961 - Loewen, Royden (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1993)
AbstractRural Canadian communities underwent profound changes as they adapted to the economic and social context after World War II. Those changes, may be described, using John Shaver's phrase, as a "Great Disjuncture". From a "centrist" point-of-view Canadian farms became more fully mechanized, products commodified and farm goals integrated with government policy. This paper focuses on the "local experience" of the "Great Disjuncture". Its subject is the Rural Municipality of Hanover in Manitoba, an ethnic community, dominated by Low German-speaking Mennonites. In Hanover traditional social relations, both on the primary level affecting gender and on the community level affecting the very idea of rurality, entered a dialectical relationship with the forces for change to create a particular localized culture. Here was an instance of cultural re-creation.